2023
DOI: 10.1111/cyt.13313
|View full text |Cite
|
Sign up to set email alerts
|

Review of the impact of the International System for Serous Fluid Cytopathology

Panagiota Mikou,
Alexandros Pergaris,
Marianne Engels
et al.

Abstract: The International System for Reporting Serous Fluid Cytology (TIS) has been proposed by an expert working team composed of the International Academy of Cytology and the American Society of Cytopathology, following an international survey. Since its introduction, the TIS has gained worldwide acceptance, and this review aims to assess its global impact. A literature search revealed 25 studies which have presented data on the impact of the TIS. Most of them provide data, including risk of malignancy (ROM) for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…data provide evidence that the standardized categorization system effectively stratifies malignancy risks, facilitating the triage of clinical management. 78 However, despite the defined diagnostic criteria, the AUS category remains a diag-nostically gray zone in effusion cytology. The definition of ND is defined, but its practical threshold varies, contributing to the wide variability in the ROM for the ND category.…”
Section: Discussionmentioning
confidence: 99%
“…data provide evidence that the standardized categorization system effectively stratifies malignancy risks, facilitating the triage of clinical management. 78 However, despite the defined diagnostic criteria, the AUS category remains a diag-nostically gray zone in effusion cytology. The definition of ND is defined, but its practical threshold varies, contributing to the wide variability in the ROM for the ND category.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of pericardial effusions has been reported in 10 studies, five of which reported ROM assessments, with the number of samples/patients ranging from 64 to 574. 24 The estimated ROM for each category was: ND, 0.0%-100.0%; NFM, 1.3%-17.4%; AUS, 0.0%-35.0%; SFM, 57.1%-100.0%; and MAL, 89.3%-100.0%. 24 The categories SFM and MAL included 20.0%-62.5% of the total cases and provided a diagnosis of malignancy with exceedingly high probability.…”
Section: The International System For Reporting Serous Fluid Cytopath...mentioning
confidence: 94%
“…To test our model in the clinical setting scenario we divided patients into high- and low-certainty groups according to the level of supporting evidence. The high-certainty group included (1) patients whose primary tumors had been resected and with a definitive routine histopathological diagnosis and (2) patients who had undergone immunohistochemical examination by paraffin sections of cell sediment, the results of which strongly suggested the origin of malignant tumors 38 , 45 , 46 . The low-certainty group consisted of (1) patients whose primary or metastasized tumors merely underwent fine-needle puncture biopsy 47 , 48 and (2) patients whose putative differential diagnosis was arrived at solely by comprehensive clinical and radiological findings.…”
Section: Methodsmentioning
confidence: 99%
“…Histological examination is used when specimens can be obtained via surgery or needle biopsy, these types of specimen providing richer diagnostic information. Cytology is mainly applicable for patients with late-stage cancer who cannot undergo surgery or tolerate needle biopsy 25 , 38 . In this scenario, specimens from pleural and peritoneal serous effusion are helpful in regard to localization of cancer origins due to their excellent accessibility 26 , 39 .…”
Section: Mainmentioning
confidence: 99%